Principles of co‐axial illumination for photochemical reactions: Part 1. Model development. Issue 2 (3rd April 2020) - Meir, Glen; Leblebici, Mumin E.; Fransen, Senne; Kuhn, Simon; Van Gerven, Tom
Abstract: Photochemical reactors with conventional homogeneous illumination suffer from a light efficiency problem, which is inherent to their design: Dark zones arise near the reagent‐rich inlet whereas the reagent depleted outlet is over‐illuminated. Any attempt to mitigate dark zones at the inlet will only increase photon losses further downstream. This study reports the principles and model equations for co‐ and counter‐current illumination in photochemical reactors, along with an optimization study to determine the most efficient and productive operating point. This work proves that the use of co‐ and counter‐current illuminated reactors increases the energy efficiency while easing scalability by implementing larger path lengths, without altering the reactor's geometry. We report a simple model to determine the conversion obtained by such novel illumination techniques and compare it to the current state‐of‐the‐art. Two nondimensional groups where derived that describe all possible reactor configurations, these are the initial absorbance ( A ) and the quantum photon balance ( ρϕ ). Variation of both parameters leads for noncompetitive photochemical reactions to an optimal point for the current state‐of‐the‐art as well as the novel co‐axial illumination. Ultimately, we recommend the use of an initial absorbance value ( A ) of at least 1, and a quantum photon balance ( ρϕ ) equal to 1 to introduce sufficient light and enable near complete absorption of light. Abstract :